Oncogenic mTOR signaling recruits myeloid-derived suppressor cells to promote tumor initiation - Welte, Thomas (Nat Cell Biol, 2016)
Myeloid-derived suppressor cells (MDSCs) play critical roles in primary and metastatic cancer progression. While MDSC regulation is widely variable even within patients harboring the same type of malignancy, the mechanisms governing such heterogeneity are largely unknown. Here, integrating human tumor genomics and syngeneic mammary tumor models, we demonstrate that mTOR signaling in cancer cells dictates a mammary tumor’s ability to stimulate MDSC accumulation through regulating G-CSF. Inhibiting this pathway or its activators (e.g., FGFR) impairs tumor progression, which is partially rescued by restoring MDSCs or G-CSF. Tumor-initiating cells (TICs) exhibit elevated G-CSF. MDSCs reciprocally increase TIC frequency through activating Notch in tumor cells, forming a feed-forward loop. Analyses of primary breast cancers and patient-derived xenografts (PDXs) corroborate these mechanisms in patients. These findings establish a non-canonical oncogenic role of mTOR signaling in recruiting pro-tumorigenic MDSCs and show how defined cancer subsets may evolve to promote and depend upon a distinct immune microenvironment.